Vztah jedinečného a modelového v politickém působení F. Udržala - Charbuský, Miloš (Univerzita Pardubice, 2002)
A significant Czech politician František Udržal was born on 3 January 1866. He entered politics in 1897 when he became a member of the Parliament in Vienna. After declaration of the Czechoslovac Republic independence on 28 October 1918 he was a member of Revolutionary National Assembly. In 1921 he was elected a minister of defence for 8 years and between 1929 and 1932 he was the Prime Minister. František Udržal was a representative of farming community. He tried to accommodate its specific interests to the interests of the whole country.
Keywords: Udržal, František; Parlament; ministerstvo obrany; agrární strana; politika